Similarities and Differences in the Effects of Toxic Concentrations of Cadmium and Chromium on the Structure and Functions of Thylakoid Membranes in Chlorella variabilis - Zsiros, Ottó; Nagy, Gergely; Patai, Roland; Solymosi, Katalin; Gasser, Urs; Polgár, Tamás F.; Garab, Győző; Kovács, László; Hörcsik, Zsolt Tibor (Frontiers in Plant Science, 2020)
Heavy-metal contaminations in natural waters, wetlands and wastewaters pose serious threats to aquatic ecosystems - mainly via targeting microalgae. In this work, we investigated the effects of toxic amounts of chromium and cadmium ions on the structure and function of the photosynthetic machinery of Chlorella variabilis cells. To halt the propagation of cells, we used high concentrations of Cd and Cr, 50-50 mg L-1, in the forms of CdCl2 x 2.5 H2O and K2Cr2O7, respectively. Both treatments led to similar, about 50% gradual diminishment of the chlorophyll contents of the cells in 48 hrs, which was, however, accompanied by a small (~10%) but statistically significant enrichment (Cd) and loss (Cr) of ß-carotene. Both Cd and Cr inhibited the activity of photosystem II (PSII) – but with more severe inhibitions with Cr. On the contrary, the PsbA (D1) protein of PSII and the PsbO protein of the oxygen-evolving complex were retained more in Cr-treated cells than in the presence of Cd. These data and the higher susceptibility of P700 redox transients in Cr-treated cells suggest that, unlike with Cd, PSII is not the main target in the photochemical apparatus. These differences at the level of photochemistry also brought about dissimilarities at higher levels of the structural complexity of the photosynthetic apparati. Circular dichroism spectroscopy measurements revealed moderate perturbations in the macro-organization of the protein complexes – with more pronounced decline in Cd-treated cells than in the cells with Cr. Also, as reflected by transmission electron microscopy and small-angle neutron scattering, the thylakoid membranes suffered shrinking and were largely fragmented in Cd-treated cells, whereas no changes could be discerned with Cr. The preservation of integrity of membranes in Cr-treated cells was most probably aided by high proportion of the de-epoxidized xanthophylls, which were absent with Cd. It can thus be concluded that beside strong similarities of the toxic effects of Cr and Cd, the response of the photosynthetic machinery of C. variabilis to these two heavy-metal ions substantially differ from each other – strongly suggesting different inhibitory and protective mechanisms following the primary toxic events.